Omega‐3 supplementation alters mitochondrial membrane composition and respiration kinetics in human skeletal muscle - Herbst, E. A. F.; Paglialunga, S.; Gerling, C.; Whitfield, J.; Mukai, K.; Chabowski, A.; Heigenhauser, G. J. F.; Spriet, L. L.; Holloway, G. P. (The Journal of physiology, 2014)
Key points Following fish oil supplementation, omega‐3 fatty acids are incorporated into cellular membranes, which may affect lipid–protein interactions and therefore the function of embedded proteins. As the components of the electron transport chain required for oxidative phosphorylation are contained in the mitochondrial membrane, omega‐3 supplementation may alter metabolic function. We supplemented male participants for 12 weeks with fish oil [eicosapentaenoic acid (EPA) and docosahexanoic acid (DHA)] and analysed mitochondrial function and reactive oxygen species (ROS) emissions in permeabilized muscle fibres from the vastus lateralis muscle. Supplementation incorporated EPA and DHA into mitochondrial membranes, but did not result in changes in maximal mitochondrial respiratory function or pyruvate respiration kinetics. However, the apparent Km for ADP was decreased following supplementation, and was independent of creatine, changes in the protein content of ADP synthase or ANT transporters. The propensity for ROS emissions increased with omega‐3 supplementation, although there were no changes in markers of lipid or protein oxidative damage. These results demonstrate that omega‐3 supplementation improves mitochondrial ADP kinetics, suggesting post‐translational modification of existing proteins. Studies have shown increased incorporation of omega‐3 fatty acids into whole skeletal muscle following supplementation, although little has been done to investigate the potential impact on the fatty acid composition of mitochondrial membranes and the functional consequences on mitochondrial bioenergetics. Therefore, we supplemented young healthy male subjects (n = 18) with fish oils [2 g eicosapentaenoic acid (EPA) and 1 g docosahexanoic acid (DHA) per day] for 12 weeks and skeletal muscle biopsies were taken prior to (Pre) and following (Post) supplementation for the analysis of mitochondrial membrane phospholipid composition and various assessments of mitochondrial bioenergetics. Total EPA and DHA content in mitochondrial membranes increased (P < 0.05) ∼450 and ∼320%, respectively, and displaced some omega‐6 species in several phospholipid populations. Mitochondrial respiration, determined in permeabilized muscle fibres, demonstrated no change in maximal substrate‐supported respiration, or in the sensitivity (apparent Km) and maximal capacity for pyruvate‐supported respiration. In contrast, mitochondrial responses during ADP titrations demonstrated an enhanced ADP sensitivity (decreased apparent Km) that was independent of the creatine kinase shuttle. As the content of ANT1, ANT2, and subunits of the electron transport chain were unaltered by supplementation, these data suggest that prolonged omega‐3 intake improves ADP kinetics in human skeletal muscle mitochondria through alterations in membrane structure and/or post‐translational modification of ATP synthase and ANT isoforms. Omega‐3 supplementation also increased the capacity for mitochondrial reactive oxygen species emission without altering the content of oxidative products, suggesting the absence of oxidative damage. The current data strongly emphasize a role for omega‐3s in reorganizing the composition of mitochondrial membranes while promoting improvements in ADP sensitivity.